Lung sequestration. CT angiography study - Campos, Néstor; Mascari, José L; Abelleira, Alfredo (Cirugía del Uruguay, 1998)
The authors make a vídeo-tape presentatíon (PAL-N, approxímately 20 minutes long) of a case of lung sequestratíon in a 14 year oíd boy; the tape mainly shows the preoperatory study performed wíth angío-TC, thís term is used for angíography obtaíned wíth the injectíon of íntravenous contrast medía and obtentíon of ímages by means of double helicoidal computerized tomography (spiral). With this technique it was possíble to identify wíth exactness anomalous arteríes coming from the aorta whích were goíng to supply the intralobar sequestratíon of the /eft inferior lung lobe, as we/1 as the outflow veín of the same section whích draíned ínto the left inferior hemiazygos.